2016
DOI: 10.1039/c6bm00271d
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in thromboresistant and antimicrobial polymers for biomedical applications: just say yes to nitric oxide (NO)

Abstract: Biomedical devices are essential for patient diagnosis and treatment; however, when blood comes in contact with foreign surfaces or homeostasis is disrupted, complications including thrombus formation and bacterial infections can interrupt device functionality, causing false readings and/or shorten device lifetime. Here, we review some of the current approaches for developing antithrombotic and antibacterial materials for biomedical applications. Special emphasis is given to materials that release or generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
258
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(259 citation statements)
references
References 303 publications
(679 reference statements)
1
258
0
Order By: Relevance
“…44,45 Furthermore, a problem with many similar bactericidal surfaces is the attachment of dead microorganisms remaining on the antibacterial coating, which can trigger immune response and inflammation, as well as block a coating’s active functional groups. 3 A unique attribute of NO releasing materials is that they can significantly reduce bacterial adhesion and prevent mature biofilm formation when released from the biomaterial surface, even at very low concentration. This may allow the bacteria to be susceptible to conventional antibiotics treatment and improve patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 Furthermore, a problem with many similar bactericidal surfaces is the attachment of dead microorganisms remaining on the antibacterial coating, which can trigger immune response and inflammation, as well as block a coating’s active functional groups. 3 A unique attribute of NO releasing materials is that they can significantly reduce bacterial adhesion and prevent mature biofilm formation when released from the biomaterial surface, even at very low concentration. This may allow the bacteria to be susceptible to conventional antibiotics treatment and improve patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…13 Such infections are extremely difficult to treat by use of antibiotics alone due to biofilm formation on the surface of the devices. Microbial biofilm consists of extracellular polymeric substances (EPS) that are known to be a physical barrier that protects bacteria from traditional antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been reported that NO treatment would cause potential antibiotic resistance. [50] Therefore, the controlled release of NO over a long period (>10 d) is desirable and will provide additional benefits for the long-term success of polymeric implants.…”
Section: Resultsmentioning
confidence: 99%
“…These effects are the result of oxidative and nitrosative stress generated by reactive intermediates of nitric oxide, resulting in damage to DNA, proteins and cell membranes. Nitric oxide is metabolized very rapidly by human metabolism in order to prevent toxicity [104,105]. In a study by Engelsman et al, monofilament polypropylene mesh was coated with a low concentration NO-releasing carbon-based coating.…”
Section: Mesh Modificationsmentioning
confidence: 99%